2018
DOI: 10.17014/ijog.5.2.117-128
|View full text |Cite
|
Sign up to set email alerts
|

Stratigraphical and Sedimentological Review of the Merawu Formation, Serayu Basin, Central Jawa, Indonesia

Abstract: Merawu Formation is widely distributed in the Serayu Basin, Central Jawa, Indonesia. The formation is dominated by fine-grained clastic sediments comprising interbedded mudstone, siltstone, and sandstone. In the field, these outcrops are well exposed and well bedded. Stratigraphically, the Merawu Formation is underlain by the Paleocene Worawari Formation and overlain by the Late Miocene Penyatan Formation. Contacts between the Merawu Formation and the Worawari Formation are always found as fault types. Twelve … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…Rambatan Formation in the western part of North Serayu Basin is equivalent to Merawu Formation located in the eastern part of the basin which generaly shows the different characters of sediments. Merawu Formation was deposited in the tidal flat to subtidal environment (Bachri, 2017;Martosuwito et al, 2018) as indicated by the presence of herring-bone and fossil tracks of cruziana (Bachri, 2017). The different lithological characteristic of Rambatan Formation from the turbidite deposits of deep sea to the tidal and subtidal environment, augmented by the geological condition since the tectonic acivities has drawn the interests for further evaluation.…”
Section: Introductionmentioning
confidence: 99%
“…Rambatan Formation in the western part of North Serayu Basin is equivalent to Merawu Formation located in the eastern part of the basin which generaly shows the different characters of sediments. Merawu Formation was deposited in the tidal flat to subtidal environment (Bachri, 2017;Martosuwito et al, 2018) as indicated by the presence of herring-bone and fossil tracks of cruziana (Bachri, 2017). The different lithological characteristic of Rambatan Formation from the turbidite deposits of deep sea to the tidal and subtidal environment, augmented by the geological condition since the tectonic acivities has drawn the interests for further evaluation.…”
Section: Introductionmentioning
confidence: 99%